ADAPTABILITAS PENORMAAN FIKIH WAKAF KE DALAM LEGISLASI NASIONAL - Yulkarnain Harahab (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2020)
AbstractThis research conducted with the aim to find out and analyze the adaptation of the formulation of fiqh waqf in national legislation, knowing, and analyzing the principles that can be drawn from the formalization of fiqh waqf into national legislation. This research is a normative juridical research that is descriptive in nature. Data collection carry out by studying documents of primary and secondary legal materials. The collected data is then analyzed qualitatively. Based on the research conducted, the following conclusions are obtained: first, the adaptability of the waqf regulation in the national legislation was shown by several things, first: the elements of waqf (waqif, nazhir, endowment property, endowment pledge, endowment allotment, and time period) waqf), management and development of waqf property, registration and reporting of waqf property, also changes in the designation and status of waqf property; second, the principles that can be drawn from the regulation of fiqh waqf into national legislation: the principle of benefit, the principle of legal certainty, the principle of professionalism, and the principle of accountability.IntisariPenelitian ini dilakukan dengan tujuan, pertama, untuk mengetahui dan menganalisis adaptabilitas penormaan fikih wakaf ke dalam legislasi nasional; kedua, mengetahui dan menganalisis prinsip-prinsip yang dapat ditarik dari penormaan fikih wakaf ke dalam legislasi nasional. Penelitian ini merupakan penelitian yuridis normatif yang bersifat deskriptif. Pengumpulan data dilakukan dengan studi dokumen terhadap bahan hukum primer dan bahan hukum sekunder. Data yang telah terkumpul selanjutnya dianalisis secara kualitatif. Berdasarkan penelitian yang telah dilakukan, diperoleh kesimpulan sebagai berikut: pertama, adaptabilitas pengaturan fikih wakaf ke dalam legislasi nasional ditunjukkan dalam beberapa hal, yaitu: unsur-unsur wakaf (wakif, nazhir, harta benda wakaf, ikrar wakaf, peruntukan wakaf, dan jangka waktu wakaf), pengelolaan dan pengembangan harta benda wakaf, pendaftaran dan pelaporan harta benda wakaf, serta perubahan peruntukan dan status harta benda wakaf; kedua, prinsip-prinsip yang dapat ditarik dari pengaturan fikih wakaf ke dalam legislasi nasional, yakni: prinsip kemaslahatan, prinsip kepastian hukum, prinsip profesionalitas, dan prinsip akuntabilitas.